Strategi Manajerial Kepala Madrasah Dalam Meningkatkan Kedisiplinan Guru di MTs.Fasthussalam - Abdulloh Hannan Mas’sum; Muhammad Sidiq Purnomo (CV. ADIBA AISHA AMIRA, 2025)
Teacher discipline is one of the key factors in creating an effective and quality educational environment. Without good discipline, the learning process in madrasahs can be disrupted, so that educational goals are not achieved optimally. Various studies show that teacher discipline has a significant effect on student achievement and learning quality. Therefore, managerial strategies implemented by madrasah principals are crucial in improving teacher discipline. This research uses a qualitative approach, the research design used is a case study. The research subjects consisted of madrasah principals, teachers, and administrative staff who have knowledge and experience related to discipline issues and managerial strategies applied. Data were collected through several techniques, including in-depth interviews, observation, and documentation.Based on the research results from interviews and observations obtained by researchers, it can be said that the principal's efforts in improving teacher discipline in the field of learning evaluation can be said to be well implemented as evidenced by the implementation of evaluations that have been carried out well by all teachers. By paying attention to the research description and the results of the research findings and discussion, the general conclusion of the research is that the efforts of the madrasah principal in an effort to improve teacher discipline have been achieved in accordance with the expected goals.